The Concept of Legal Intensity: Harmonizing God’s Rule within Constitutional Law - Arlis, Arlis (Universitas Islam Negeri Walisongo Semarang, 2023)
The study aims to discover the idea of legal intensity in the context of the harmonization of God's rule into Constitutional Law. The method used is qualitative. The results showed that the idea of legal intensity in the context of harmonising God's rule into Constitutional Law is necessary. The harmonization is in line with the theory of the purpose of the law for the benefit of servants in the world and the hereafter. Constitutional law during the Prophet Muhammad SAW is the best example. The legal intensity regulates how to achieve a better life, specifically constitutionality. When the country's laws are of superior quality, then Allah Swt will prosper the country. The provisions in Article 29 Paragraph 1 of the Constitution of the Republic of Indonesia of 1945 state that the state based on the One True God in substance contains the principle of tawhid by God's rules. Students' views on harmonising God's rule into Indonesian Constitutional Law generally agree with the idea of legal intensity. The idea of legal intensity among them has universal criteria: the path of God Almighty's rule, sincerity, gratitude, bound by promises to God, with God, fitrah, quality of law, scientific responsibility, Adat basandi syara' syara' basandi kitabullah syara' mangato adat mamakai. Students agreed because the idea of legal intensity was very good and influential in realizing the state's goals.Penelitian bertujuan untuk menemukan gagasan intensitas hukum dalam konteks harmonisasi aturan Tuhan ke dalam Hukum Tata Negara. Metode yang digunakan adalah kualitatif. Hasil penelitian menunjukkan bahwa gagasan intensitas hukum dalam konteks harmonisasi aturan Tuhan ke dalam Hukum Tata Negara sangat diperlukan. Harmonisasi tersebut sejalan dengan teori tujuan hukum untuk kesejahteraan hamba di dunia dan akhirat. Hukum tata negara pada masa Rasulullah SAW merupakan contoh terbaik. Intensitas hukum mengatur cara mencapai kehidupan yang lebih baik, khususnya tentang konstitusionalitas. Ketika hukum negara berkualitas unggul, maka Allah Swt akan memberkahi negara tersebut. Ketentuan dalam Pasal 29 Ayat 1 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 menyebutkan bahwa negara berdasarkan Ketuhanan Yang Maha Esa secara substansi mengandung prinsip tauhid oleh aturan Tuhan. Pandangan mahasiswa tentang harmonisasi aturan Tuhan ke dalam Hukum Tata Negara Indonesia umumnya setuju dengan gagasan intensitas hukum. Gagasan intensitas hukum di antara mereka memiliki kriteria universal: jalur aturan Tuhan Yang Maha Esa, ikhlas, syukur, terikat oleh janji kepada Tuhan, bersama Tuhan, fitrah, mutu hukum, tanggung jawab ilmiah, Adat basandi syara' syara' basandi kitabullah syara' mangato adat mamakai. Mahasiswa setuju karena gagasan intensitas hukum sangat bagus dan berpengaruh dalam mewujudkan tujuan negara.